Analisis Kadar O6 -[H3 ]Metilguanin-DNA pada Kultur Hepatosit Tikus Menggunakan Liquid Scintillation Counter Setelah Pemberian (-)-Epigalokatekin Galat dari Teh Hijau - Purwanto, Djoko Agus (Jurnal Kedokteran Indonesia, 2011)
Background: Alkylation of DNA can occur at various site, however alkylation of the O6-position ofguanine has the strongest mutagenic potential. O6-Methylguanine is a toxic and mutagenic lesionwhich is formed in cellular DNA by alkylating agents. Alkyl group from carbanium ion can attack DNAforms alkylated DNA especially at O6 position of guanine. O6-methylguanine mispairs with thymineduring replication, and if the adduct is not removed, this results in conversion from a guanine-cytosinepair to an adenine-thymine pair. Deficient repair of O6-methylguanine has been suggested to be acontributory factor in the etiology of some diseases such as diabetes and cancer. This study aimed todetermine O6-methylguanine DNA concentration induced by N-[H3]methyl-N-nitrosourea ([H3]MNU)in rat liver cell culture with and without (-)-epigalocatechin gallate exposure.Methods: Primary rat liver cell culture was divided into 10 groups. Five groups for [H3]MNU 32 μMexposure, and 5 groups remain for 48 μM [H3]MNU exposure. Each group of [H3]MNU exposure gotEGCG 0 (as control), 8, 17, 33 and 67 ppm. The DNA was isolated, and O6-[H3]methylguanine DNAseparated by high performance liquid chromatography (HPLC). Concentration of O6-[H3]methylguanineDNA was measured by Liquid Scintillation Counter.Results: O6-Methylguanine DNA concentration decreased significantly in liver cell culture groups withEGCG. O6-[H3]Methylguanine DNA concentration in control groups for [H3]MNU 32 μM and 48 μMwere 29.89 ± 2.01 and 32.00 ± 1.67 fmol/μg DNA, respectively, while with EGCG 67 ppm were 1.87 ± 0.94and 2.38 ± 0.36 fmol/μg DNA.Conclusion: O6-methylguanine DNA concentration in liver rat culture induced by MNU decreasessignificantly after EGCG exposure. These findings support the conclusion that EGCG plays a key role insuppressing and inhibiting cancer development.Keywords:(-)-epigalocatechin gallate, N-[H3]methyl-N-nitrosourea, O6-methylguanine DNA, LiquidScintilation Counter